Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/ajh.24452
|View full text |Cite
|
Sign up to set email alerts
|

FISHing in the dark: How the combination of FISH and conventional karyotyping improves the diagnostic yield in CpG‐stimulated chronic lymphocytic leukemia

Abstract: Despite significant advances in molecular genetic approaches, fluorescence in situ hybridization (FISH) remains the gold standard for the diagnostic evaluation of genomic aberrations in patients with chronic lymphocytic leukemia (CLL). Efforts to improve the diagnostic utility of molecular cytogenetic testing have led to the expansion of the traditional 4-probe CLL FISH panel. Not only do these efforts increase the cost of testing, they remain hindered by the inherent limitations of FISH studies -namely the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…The results obtained showed that conventional karyotyping should be included in the observation of clonal evolution in addition to the FISH technique. These observations confirm the suggestions of many researchers that the assessment of risk of the clinical course of the disease and monitoring the treatment of patients with CLL indicate the need to include conventional karyotyping for screening these patients, similarly to those routinely performed in other hematological disorders [21,28].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results obtained showed that conventional karyotyping should be included in the observation of clonal evolution in addition to the FISH technique. These observations confirm the suggestions of many researchers that the assessment of risk of the clinical course of the disease and monitoring the treatment of patients with CLL indicate the need to include conventional karyotyping for screening these patients, similarly to those routinely performed in other hematological disorders [21,28].…”
Section: Discussionsupporting
confidence: 86%
“…The detection of these changes has increased dramatically in recent years by the introduction of stimulating agents, such as DSP30/IL2, in cell cultures. [21]. The phenomenon of clonal evolution was more frequently observed with the use of a more sensitive method, namely the FISH technique [20,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence in situ hybridization (FISH) is simple, reliable and cost-effective and therefore FISH is a major technology that is widely applied for clinical diagnosis, especially for hematologic malignancies, even in the era of next-generation sequencing (NGS) [1][2][3][4]. In the Clinical Cytogenetics Laboratory at MD Anderson Cancer Center, over 15,000 FISH tests are performed each year, including approximately 1,000 BCR-ABL1 and 500 MYC FISH tests, respectively.…”
Section: Fluorescence In Situ Hybridizationmentioning
confidence: 99%
“…Taking into account the CBA in LR-FISH group, 28% of cases might be reclassified in intermediate risk category (n = 90) and 7% in defavorable risk category (n = 24). The observation of additional chromosome abnormalities in LR-FISH category had previously been noticed 19,20. Indeed, one to two additional chromosomal anomalies were reported to be sufficient to modify time to first treatment and even overall survival independently if the number of anomalies is exclusively superior to 3 21.…”
mentioning
confidence: 89%